Tax Planning, Conservatism Accounting and Business Risk on Company Value - Nugroho, Wawan Cahyo (E-Jurnal Akuntansi, 2025)
This study aims to examine the effect of tax planning, accounting conservatism, and business risk on firm value. This study used 124 samples from 31 property companies listed on the Indonesia Stock Exchange in 2020-2023. The data analysis technique used multiple linear regression. The results of the study showed that tax planning had no significant effect on firm value. This is because aggressive tax planning can cause investors to lose confidence, thus reducing investment interest. Accounting conservatism has a significant positive effect on firm value because the principle of conservatism can reduce agency conflicts, allowing investors to make decisions based on the resulting financial statements, thus providing high value to the company. Business risk has a significant positive effect on firm value. This is because companies that are able to manage risk well demonstrate their resilience to market changes and flexibility, as well as the ability to overcome problems, thereby increasing confidence in the company's future. Keywords: Tax Planning, Conservatism Accounting, Business Risk, Firm Value